Potential Invasive Pests of Agricultural Crops 2013
DOI: 10.1079/9781845938291.0373
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of exotic arthropods in South America's biodiversity hotspots and agro-production systems.

Abstract: This chapter presents a study attempting to document the most significant arthropod invasions in mainland South America, with particular emphasis on scales (e.g., Coccidae, Diaspididae and Pseudococcidae). A regional species inventory was developed, based upon (gray) literature revision, and employed niche modelling to visualize the geographical distribution of (potentially) some of the most worrisome species. A broad literature revision was carried out to screen invasive species records in mainland South Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Most of the scale insect species that were identified are exotic and polyphagous. However, the neotropical species Leptococcus minutus (Hempel) (Pseudococcidae) has been associated only with host plants of the genus Citrus, for which native host plants have not yet been documented (Wyckhuys et al 2013;García Morales et al 2016). Praelongorthezia praelonga and F. virgata, also of Neotropical origin, are polyphagous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the scale insect species that were identified are exotic and polyphagous. However, the neotropical species Leptococcus minutus (Hempel) (Pseudococcidae) has been associated only with host plants of the genus Citrus, for which native host plants have not yet been documented (Wyckhuys et al 2013;García Morales et al 2016). Praelongorthezia praelonga and F. virgata, also of Neotropical origin, are polyphagous.…”
Section: Resultsmentioning
confidence: 99%
“…They probably were transported along with their host plants when the latter were first introduced into South America and Brazil (Martinelli et al 2014). These invaders are mostly polyphagous (Wyckhuys et al 2013), and around the world generally are associated with 3 to 12 citrus species (Garcia Morales et al 2016), demonstrating the lack of specificity of these insects to particular Citrus spp. The large host range of these insects facilitated their establishment in both rural and urban areas, as was observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The species was found only at high altitudes above 1,000 m. This is a generalist and invasive pest species spread on tropical and subtropical regions under anthropogenic activities (Wyckhuys et al 2013); it is reported in many countries in the Neotropics, including Brazil (Granara de Willink et al 2010, García Morales et al 2016 where it has been related occurring in several hosts in the States of Bahia, Espírito Santo, Minas Gerais, Pará, Paraná, Rio de Janeiro, Rio Grande do Norte, Rio Grande do Sul, Santa Catarina and São Paulo (Table SI). MAURÍCIO J. FORNAZIER et al Coccus viridis has a great capacity for colonization and adaptation in new areas that may be attributed to their habits of polyphagy and parthenogenetic reproduction (Malumphy and Treseder 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Studying invasive species in these systems can help developing countries to protect their most valuable resources and provide measures against threats posed to their economy by these organisms. However, there is little research on insect invasions in South America [ 19 , 20 ] and in high elevation agroecosystems [ 21 ].…”
Section: Introductionmentioning
confidence: 99%